2014
DOI: 10.1002/elan.201400171
|View full text |Cite
|
Sign up to set email alerts
|

Selective, Nanomolar Electrochemical Determination of Environmental Contaminants Dihydroxybenzene Isomers Found in Water Bodies Using Nanocrystalline Zeolite Modified Carbon Paste Electrodes

Abstract: Nanocrystalline zeolites of different framework structures were prepared by the addition of suitable structure directing agents in the synthesis composition of conventional zeolites. Zeolite modified carbon paste electrodes were constructed for the simultaneous determination of dihydroxybenzene isomers. Nanocrystalline zeolite Beta modified carbon paste electrode exhibited the highest electrocatalytic activity. Under optimum conditions, wide linear range was obtained from 150 nM to 400 µM with lower detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…This increase in peak intensity can be attributed to increased electroactive area, increased diffusion coefficient, and decreased double-layer capacitance resistance at the electrode-solution interface of ZMCPE6. The maximum peak current observed for the amount of 3.5 grams can be attributed to the high amounts of Si-OH and Al-OH groups present on the electrode surface, producing a maximum current at 3.5 g. At quantities exceeding this value, saturation of the electrode surface occurred, reducing the peak current [43]. …”
Section: Influence Of Zeolite Amount On Peak Current (I P )mentioning
confidence: 82%
“…This increase in peak intensity can be attributed to increased electroactive area, increased diffusion coefficient, and decreased double-layer capacitance resistance at the electrode-solution interface of ZMCPE6. The maximum peak current observed for the amount of 3.5 grams can be attributed to the high amounts of Si-OH and Al-OH groups present on the electrode surface, producing a maximum current at 3.5 g. At quantities exceeding this value, saturation of the electrode surface occurred, reducing the peak current [43]. …”
Section: Influence Of Zeolite Amount On Peak Current (I P )mentioning
confidence: 82%
“…Our research is focused on the development of mesoporous polyaniline [14][15][16][17], metal oxides [18][19][20][21], and zeolites [22][23][24][25] based nanocomposite materials. For the synthesis of HAP based nanocomposite materials, it is important to choose a suitable biocompatible material that inculcates sites for the nucleation and growth of HAP.…”
Section: Introductionmentioning
confidence: 99%
“…These electrodes provided satisfactory results even for various environmental water samples . Large pore diameter and large external surface area of nanocrystalline Beta were accountable for the high electrocatalytic activity compared to other zeolite materials explored in this study.…”
Section: Metal Oxides and Zeolite Based Electrochemical Sensors For Ementioning
confidence: 76%
“…Rajendra and co‐authors have reported zeolite (Nano‐Beta, Nano‐ZSM‐5, and Nano‐LTA) modified carbon paste electrodes for the simultaneous electrocatalytic oxidation of HQ, CC, and RC with high selectivity. These electrodes provided satisfactory results even for various environmental water samples .…”
Section: Metal Oxides and Zeolite Based Electrochemical Sensors For Ementioning
confidence: 90%